TANGGUNG JAWAB MERCHANT SHOPEE DALAM TRANSAKSI COD MENURUT HUKUM PERLINDUNGAN KONSUMEN - Stella Trixie Jane; Anna Maria Tri Anggraini (Fakultas Hukum Universitas Trisakti, 2021)
One of the fast-growing e-commerce sites in Indonesia is Shopee. Shopee provides a Cash on Delivery (COD) payment method. The application of COD in fact gets a lot of public attention, because many consumers vent their anger at the courier because the goods sent do not match the order. The formulation of this problem is How are the legal consequences of business actors in Shopee application-based buying and selling transactions through Cash on Delivery (COD) for goods sent that are not in accordance with orders according to Law Number 8 of 1999 concerning Consumer Protection and related regulations? And how is the responsibility of business actors in buying and selling transactions based on the Shopee application through Cash on Delivery (COD) for goods that are sent not in accordance with the order according to Law Number 8 of 1999 concerning Consumer Protection and related regulations? Normative research method, analyzed using qualitative methods with deductive inference. The results of the research, discussion and conclusion, that the legal consequences of the Shopee application-based buying and selling transaction through COD, the business actor provides compensation and consumers can make complaints, and the responsibility of the business actor is contractual responsibility.